Informing educators by examining the features of Russian-Tatar relation coverage by Tatar historians - Minnegosmanovich Fazliev, Aivaz (2021)
A special place belongs to the historical thought of the late 19th - early 20th centuries in the spiritual heritage of the Tatar people. In a short time, Tatar historians have achieved significant results in the reconstruction and study of the national past. Their successes were appreciated by Russian and European scholars and orientalists, and their unconditional leadership among other Turkic Muslims was generally recognized. The works by Sh. Mardzhani, R. Fakhrutdinov, G. Akhmarov, H. Atlasi, G. Gubaidullin are being republished today and are returned to the reader. Their work is being successfully studied, but there are no works where the formation and development of Tatar historical science at the end of the 19th - beginning of the 20th centuries would be considered specifically. A systematized study of the historical thought of the Tatars during the Jadid period, the determination of the characteristics, trends, and the directions of its development remains an urgent task of modern science. This scientific article examines the features of Russian-Tatar relation coverage by Tatar historians of the late 19th - early 20th centuries, reveals the information and analytical activities of censorship and its special attention to historical writings, contains an overview of little-known sources - popular editions and publications in time-based press, dated to the centenary of The Patriotic War of 1812 and the 300th anniversary of the House of Romanov, the authors of which, showing the commonality of the historical fate of Russians and Tatars, substantiated the thesis of "equal rights in a common Fatherland".  The obtained analytical results are very effective in increasing the level of education of educators in this field.